2020
DOI: 10.7454/jki.v0i0.598
|View full text |Cite
|
Sign up to set email alerts
|

Changes in The Signs, Symptoms, and Anger Management of Patients with A Risk of Violent Behavior After Receiving Assertive Training and Family Psychoeducation Using Roy’s Theoretical Approach: A Case Report

Abstract: Mental disorders are predicted to increase every year. Patients with severe mental disorders, such as schizophrenia, often engage in violent behavior. The treatment of such patients can use general nursing treatments (anger management with physical therapy, taking medicines regularly, and verbal and spiritual methods) and specialist nursing interventions (assertive training and family psychoeducation). This case report involved 11 patients, with the majority aged between 26 and 60 years, unemployed, high schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Increasing awareness of the importance of the benefits of the skills trained can increase the motivation of clients to practice those abilities. Other studies have also shown that nursing measures can improve the ability to control violent behavior (Fahrizal et al, 2020). Psychoeducational methods Online It is considered more appropriate if applied during the COVID-19 pandemic considering that there are several advantages also mentioned in this study, including the need for lower costs, convenience, the possibility of family informants to be able to join through video conference multi-point and a lower risk of spreading infection.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing awareness of the importance of the benefits of the skills trained can increase the motivation of clients to practice those abilities. Other studies have also shown that nursing measures can improve the ability to control violent behavior (Fahrizal et al, 2020). Psychoeducational methods Online It is considered more appropriate if applied during the COVID-19 pandemic considering that there are several advantages also mentioned in this study, including the need for lower costs, convenience, the possibility of family informants to be able to join through video conference multi-point and a lower risk of spreading infection.…”
Section: Discussionmentioning
confidence: 99%
“…Klien yang menunjukkan tanda gejala tersebut tidak memiliki kemampuan mengontrol emosi atau marah, sehingga berujung pada munculnya perilaku kekerasan. Semakin baik kemampuan mengontrol perilaku kekerasan, maka semakin sedikit pula tanda gejala yang muncul (Fahrizal, Mustikasari, & Daulima, 2020). Kemampuan individu (personal ability) merupakan salah satu cara yang dapat dikembangkan untuk mencegah perilaku kekerasan (Setiawan, Keliat, & Wardani, 2015).…”
Section: Pendahuluanunclassified